Information seeking behavior among perinatal women: a systematic review - Li, Miaomiao; Wan Abas, Wan Anita; Marof, Aini Azeqa; Liu, Lu (Redfame Publishing, 2023)
The health of perinatal women is critical to maternal well-being and infant development. Understanding how perinatal women seek health information is essential for providing effective antenatal and postnatal care. However, there is a lack of systematic reviews on this topic. This study aimed to conduct a comprehensive literature review of existing research following the PRISMA-SCR guidelines. The results showed that perinatal women commonly seek pregnancy-related health information. Interpersonal sources were identified as the primary and most trusted sources of information. The study also identified various factors and barriers that influence health information seeking, including individual, socio-cultural, structural, and information-related factors, with personal responsibility for health being an influential factor that has not been emphasized previously. It provides valuable insights into the health information seeking behavior of perinatal women. The influence of personal health responsibility, social power dynamics and socio-cultural norms on health information seeking needs to be further investigated.